HUBUNGAN INTERNAL KEAGAMAAN DALAM ISLAM MENURUT TUNTUNAN AL-QUR'AN - Soufyan Ibrahim (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2017)
The construction of formulations that the Qur'an offers as a basic source of Islamic teachings on the ethical-religious format in the context of worship as the embodiment of the obligation of morality towards God is explicitly reflected in various formulations. The Qur'an in this context affirms among other obligations that must be embraced by human beings in relation to God, which is a command to always be grateful for the various blessings given by Allah, since he was born from the mother's belly in the state of not knowing anything, Until Allah created various facilities that can be used in everyday life. Another thing that is also explained in the verse is the command that man can run various guidance and guidance of religion properly and correctly and follow the religion that He approves.